2020
DOI: 10.1088/1361-6463/ab5883
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the resistive switching of BiFO3 thin films through electrical stressing

Abstract: The resistive switching (RS) of Au/BiFeO 3 /SrRuO 3 samples was shown to be controllable by using a thermal treatment and an electrical stressing method. Such a modulation of resistive switching effect can be associated to the oxygen vacancy movement and redistribution within the BiFeO 3 thin film and the trapping/detrapping of charge carriers at the interfaces. After the application of a negative voltage to the thin film for a stressing period, a resistive switching reversal effect occurred and the current re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Lomenzo et al [26,27] suggested that the decreased dielectric constant in the wake-up state was caused by the tetragonal-to-ferroelectric orthorhombic phase transition. Pintilie et al proposed that the C-V curve of a ferroelectric material can be expressed by [17,28]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lomenzo et al [26,27] suggested that the decreased dielectric constant in the wake-up state was caused by the tetragonal-to-ferroelectric orthorhombic phase transition. Pintilie et al proposed that the C-V curve of a ferroelectric material can be expressed by [17,28]…”
Section: Resultsmentioning
confidence: 99%
“…Because the V Ö with positive charges can attract electrons, they usually act as electron-trapping centers. [17] Initially, the V Ö accumulated at the TiN/HZO interface (Fig. 5(a)), where a large number of electrons were needed to fill traps, causing a small density of free charge in the space-charge region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased presence of oxygen vacancies create localized intraband gap defect states (e.g., F-centers and F 0 -centers) that significantly alter the p–d charge transfer transitions and subsequently reduce the band gap . The increased vacancy concentration manifests as both lower SET (threshold) voltage and improved switching uniformity for nanocrystal assemblies, similar to recent studies of LaAlO 3 , LaMnO 3 , and BiFeO 3 …”
Section: Resultsmentioning
confidence: 99%
“…50 The increased vacancy concentration manifests as both lower SET (threshold) voltage and improved switching uniformity for nanocrystal assemblies, similar to recent studies of LaAlO 3 , 51 LaMnO 3 , 52 and BiFeO 3 . 53 Trap-Mediated Space-Charge-Limited Current. The current−voltage responses of the 10 BZO-SZO combinations (Figure 2b,c, Figure S4, and Figure S6) were plotted on a log− log scale and fitted to determine the governing switching mechanism(s).…”
Section: ■ Results and Discussionmentioning
confidence: 99%